Computational Intelligence International Joint Conference, IJCCI 2016 Porto, Portugal, November 9-11, 2016 Revised Selected Papers - Merelo, Juan Julian; Melício, Fernando; Cadenas, José M.; Dourado, António; Madani, Kurosh; Ruano, António; Filipe, Joaquim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers revised and extended versions of the best papers presented at the 8th International Joint Conference on Computational Intelligence (IJCCI 2016), which was held in Porto, Portugal from 9 to 11 November 2016. The papers address three main fields of Computational Intelligence, namely: Evolutionary Computation, Fuzzy Computation, and Neural Computation. In addition to highlighting recent advances in these areas, the book offers veteran researchers new and innovative solutions, while also providing a source of information and inspiration for newcomers to the field.
An Adapting Quantum Field Surrogate for Evolution Strategies -- DynaGrow: Next Generation Software for Multi-Objective Energy Cost-Efficient Control of Supplemental Light in Greenhouses -- A System for Evolving Art using Supervised Learning and Aesthetic Analogies -- Particle Convergence Expected Time in The Stochastic Model of PSO -- Evolution of Mobile Strategies in Social Dilemma Games: An Analysis of Cooperative Cluster Formation -- The Impact of Coevolution and Abstention on the Emergence of Cooperation -- Advances in the Evolution of Complex Cellular Automata -- Fuzzy Modeling, Control and Prediction in Human-Robot Systems -- Classification Confusion within Nefclass Caused by Feature Value Skewness in Multi-dimensional Datasets -- Hyperresolution for Propositional Product Logic with Truth Constants -- Fuzzy Clustering of High Dimensional Data with Noise and Outliers -- E-mail Spam Filter based on Unsupervised Neural Architectures and Thematic Categories -- A Noise Compensation Mechanism foran RGNG-based Grid Cell Model -- A Possible Encoding of 3D Visual Space in Primates.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence